33‐2: Development of the Free‐Form Curved IPS LCD using Stress Retardation Analysis for Automotive Applications. Issue 1 (2nd June 2017) - Park, SeHong; Park, JongSin; Lee, TaeRim; Jun, MyungChul; Kang, InByeong
Abstract : The Curved TFT‐LCDs on glass are mainly single curved shape, while the free‐form curved displays (FFCDs) are mainly OLED displays on plastic substrate. Multi‐curvature TFT‐LCDs using glass are difficult to manufacture due to substrate interaction, breakage and mura caused by stress from curving of the glass. Particularly, the waterfall shape which simultaneously consists of concave and convex forms causes the light leakage that increases the retardation of LCDs due to the substrate interaction. The TFT‐LCDs can implement the multi‐curved shape if the stress retardation is improved. Therefore, we tried to simulate stress retardation through the light leakage analysis of curved LCDs. We have developed IPS LCDs with the 25‐inch waterfall‐like curved 500R, the 21.5‐inch L‐curved 600R and the 14.45‐inch convex curved 1000R of trapezium shape for the automotive platform design